Suppression of Red Blood Cell Autofluorescence for Immunocytochemistry on Fixed Embryonic Mouse Tissue - Whittington, Niteace C; Wray, Susan (Current protocols in neuroscience, 2017)
Autofluorescence is a problem that interferes with immunofluorescent staining and complicates data analysis. Throughout the mouse embryo, red blood cells naturally fluoresce across multiple wavelengths, spanning the emission and excitation spectra of many commonly used fluorescent reporters, including antibodies, dyes, stains, probes, and transgenic proteins, making it difficult to distinguish assay fluorescence from endogenous fluorescence. Several tissue treatment methods have been developed to bypass this issue with varying degrees of success. Sudan Black B dye has been commonly used to quench autofluorescence, but can also introduce background fluorescence. Here we present a protocol for an alternative called TrueBlack Lipofuscin Autofluorescence Quencher. The protocol described in this unit demonstrates how TrueBlack efficiently quenches red blood cell autofluorescence across red and green wavelengths in fixed embryonic tissue without interfering with immunofluorescent signal intensity or introducing background staining. We also identify optimal incubation, concentration, and multiple usage conditions for routine immunofluorescence microscopy. © 2017 by John Wiley & Sons, Inc.